CD14+CD16+ monocytes in coronary artery disease and their relationship to serum TNF-α levels - Schlitt, Axel; Heine, Gunnar H.; Blankenberg, Stefan; Espinola-Klein, Christine; Dopheide, Joern F.; Bickel, Christoph; Lackner, Karl J.; Iz, Mete; Meyer, Juergen; Darius, Harald; Rupprecht, Hans J. (Thrombosis and Haemostasis, 2004)
Monocytes play a central role in the inflammatory disease atherosclerosis. CD14+CD16+ monocytes are considered proinflammatory monocytes, as they have an increased capacity to produce proinflammatory cytokines, such as TNF-α, and are elevated in various inflammatory diseases. We hypothesized that patients with coronary artery disease (CAD) have increased levels of CD14+CD16+ monocytes, and that CD14+CD16+ monocytes are associated with inflammation markers. We investigated CD14+CD16+ monocytes in 247 patients with CAD and 61 control subjects using flow cytometry. In addition serum concentrations of TNF-α, IL-6, and Hs-CRP were assessed. Patients with CAD had higher levels of CD14+CD16+ monocytes than controls (13.6% versus 11.4%; p<0.001). Logistic regression analysis including quartiles of CD14+CD16+ monocytes showed that CD14+CD16+ monocytes were associated with prevalence of CAD (OR 4.9, 95% CI 2.5–19.1, for subjects in the fourth quartile in comparison to subjects in the first quartile). The association between CD14+CD16+ monocytes and CAD remained independently significant after adjustment for most potential confounders (OR 5.0, 95% CI 1.2-20.0). Serum concentrations of TNF-α were elevated in subjects within the highest quartiles of CD14+CD16+ monocytes (p=0.018). Our study showed that increased numbers of CD14+CD16+ monocytes are associated with coronary atherosclerosis and TNF-α. In accordance, recent animal studies suggest a possibly important role of these monocytes in the development of atherosclerosis.
Keywords: CD14+CD16+ monocytes; TNF-alpha; coronary artery disease